Ganglion cell layer measurements correlate with disease severity in patients with Alzheimer's disease. (19th February 2016) - Garcia‐Martin, Elena; Bambo, Maria P.; Marques, Marcia L.; Satue, Maria; Otin, Sofia; Larrosa, Jose M.; Polo, Vicente; Pablo, Luis E.
Abstract: Purpose: To evaluate the thickness of the 10 retinal layers of patients with Alzheimer's disease (AD) using a new segmentation technology of the Spectralis optical coherence tomography (OCT) and to determine whether the thickness of specific layers predicts neurodegeneration or AD severity. Methods: Patients with AD ( n = 150) and age‐matched healthy controls ( n = 75) were analysed using the segmentation application prototype to automatically segment all retinal layers in a macular scan. Thicknesses of each layer were compared between patients with AD and controls, and between patients with disease durations of less than or at least 3 years. Associations between retinal layer thicknesses, disease duration and AD severity were evaluated. Results: Patients with AD had reduced thickness in the retinal nerve fibre, ganglion cell, inner plexiform and outer nuclear layers (p < 0.05). The inner retinal layers were more affected in patients with long disease duration. Ganglion cell and retinal nerve fibre layer thicknesses were inversely correlated with AD duration and severity. Ganglion cell and inner plexiform layers thicknesses were predictive of axonal damage. Conclusions: The segmentation application revealed ganglion cell and retinal layer atrophy in patients with AD compared with controls, especially in the inner layers of patients with long disease duration. Ganglion cell layer reduction was associated with increased axonal damage and may predict greater disease severity.